Childhood non-Hodgkin’s lymphoma in Cipto Mangunkusumo Hospital, Jakarta: Outcome of treatment 2000-2005 - Djajadiman Gatot; Teny Tjitrasari; Novie Amelia Chozie (Paediatrica Indonesiana, 2006)
Background Childhood non-Hodgkin’s lymphoma (NHL) is the thirdmost common solid tumor in Cipto Mangunkusumo, Jakarta. Since1992 there was no national report on the survival of children withNHL. To continue our observation on the result of treatment of chil-dren with NHL in our institution, we briefly report the outcome therapyof children with NHL who were admitted to our hospital during 2000-2005.Objective All patients who were diagnosed as non-Burkitt type NHLbetween January 2000-December 2005 were included in the study.Data collected retrospectively from the Oncology Registration ofHematology-Oncology Division, Department of Child Health, CiptoMangunkusumo Hospital, including age, sex, primary site of tumor,histopathology type, staging, treatment response, and outcome.Results A total of 24 patients were available. Male:female ratiowas 1.8:1. The age range was from 9 months to 11 years (median6 years). The histological type consisted of LL (3) and non-LL (11).Ten out of 14 patients were diagnosed as advanced stages (stagesIII and IV), while the rest were in stage II. Primary tumor site in LLtype were the head and neck (1), mediastinum (1), and testis (1),while the non-LL type patients had more varied site. Overall sur-vival of NHL was 78.6%+4.7%.Conclusion The overall survival of childhood NHL patients treatedwith protocol in our institution is in the range of survival that hadachieved in other centers worldwide, even with advanced stage ofdisease.